The effect of a single dose of fumonisin B1 on rat kidney - Peraica, Maja (Array, 2008)
Summary: It is known that exposure to mycotoxin fumonisin B1 (FB1) causes apoptosis and increases lipid peroxidation in the kidney of experimental animals. In this study, adult male Wistar rats were given a single dose (5, 50, 500 mg per kg of body mass) by gavage and sacrificed 4, 24 and 48 hours after dosing. The parameters of oxidative stress, sphingolipids, DNA lesions and histopathological changes were checked in the kidney of treated and control animals. The metabolism of sphingolipids was significantly affected with the lowest FB1 dose (sphinganine/sphingosine: 2.53 ± 0.52 vs. control 0.62 ± 0.10), while even the highest dose did not change the parameters of oxidative stress. DNA lesions measured as comet tail length (range (13.6 ± 0.41) mm to (19.83 ± 1.43) mm) and tail intensity ((0.60 ± 0.16) % to (2.74 ± 0.17) %) were FB1 dose- and time-dependent. Apoptotic cells and mitotic figures were found in the cortical and outer stripe of the medullar part of the kidney